FEATURES OF HIGHER EDUCATION MANAGEMENT IN IRAN (EDUCATION IN THE 21ST CENTURY, 2024)
Higher education in every country has a special place and role in the process of educational, technological, cultural, socio-economic development of the society, it greatly influences other levels and formats of the education system of the given country, such as informal, lifelong (continuous) and adult education. Adult education is based on the main approach that learning is not limited to a certain level of education, but is a continuous process. The purpose of the article is to thoroughly study and analyze the management features and challenges of Iran's higher education system, as well as its importance in adult education. The methods used by us are: the study of sources and documents, data analysis.The scientific novelty of the research is that the current state of Iran's education system, policies and curricula, gaps and challenges were comprehensively analyzed, and in that context, the problems and shortcomings of adult education in Iran were highlighted and evaluated.The main problem has also been studied by Abtahi Seyed Hossein, Bagherimoghadam Nasser, Isazadeh Ebrahim, Ghurchian Nadergholi, Nafisi Abdulhossein, whose views also played a role in the development of higher education in Iran, also studied the basic problem.
Keywords: Iranian higher education; education management; system; continuing education; university; challenges; development; reforms